АДМІНІСТРАТИВНО-ТЕРИТОРІАЛЬНЕ РАЙОНУВАННЯ ТА ОСОБЛИВОСТІ СТРУКТУРИ ПІВДЕННО-БУЗЬКОГО ЕКОКОРИДОРУ - Совгіра С. В.; Гончаренко Г. Є. (World Science, 2018)
The article reveals the structure of the Southern Bug ecological corridor. It is established that it is solid, it occupies the course of the Southern Bug, the floodplain and floodplain terraces of its river valley, partly sloping terrain. The administrative-territorial division of the Southern Bug ecocorridor was carried out. According to the regional specifics, its territory is structured into 8 plots. The upper part (Upper Pobuzhzhia) includes 1-3 plots - from village Holodets (leakage) to the mouth of the river Desna, medium (Average Pobuzhzhia) - 4-6 plots - from the mouth of the river Desna to the city of Pervomaisk (the confluence of the river Sinyukhi in the South Bug river), the lower (Lower Pobuzhya) - 7 -8 sites - from the city of Pervomaysk to the lower reaches of the Nikolaev city. It was established that each site is characterized by considerable mosaic and heterogeneity of natural conditions and landscape complexes. It is proved that South-Bug ecocorridor combines elements of regional ecological networks of Vinnytsia, Khmelnytsky, Kirovograd, Cherkasy, Odesa and Mykolaiv regions.